LANDSCAPE OF VISUAL AI IN INDONESIA'S CREATIVE INDUSTRY: BETWEEN INNOVATION OPPORTUNITIES AND ETHICAL REGULATORY CHALLENGES - Salam, Muhammad Fachrul; Hany Alexandra; Nurul Amalia S; Mohamad Alfauzan Azzubaidi; Dwi Adinda Irfa (International Journal of Cultural and Social Science, 2025)
The rapid development of generative visual AI in Indonesia's digital creative ecosystem has outpaced clear ethical and regulatory frameworks, creating a landscape of opportunities rife with uncertainty. This study maps these complex dynamics using a mixed-methods explanatory sequential design. The quantitative phase involved an online survey of 322 respondents, followed by a qualitative phase through in-depth interviews with 10 selected respondents. The findings indicate a high but pragmatic level of AI adoption (96.6%). There is a strong paradox between enthusiasm for the benefits of AI (Mean > 4.3) and deep concerns about ethical risks (Mean > 4.1), particularly regarding originality. A significant gap was identified between high personal ethical awareness and low understanding of formal regulations (Mean < 3.8). The practical implication of this study is the urgent need to develop ethical guidelines and legal literacy modules for creators in Indonesia.